Deteksi Varian Rhesus Dweak pada Populasi Rhesus Negatif di Provinsi DKI Jakarta - Endang Pratiwi; Ni Ken Ritchie; Heri Wibowo (MEDIA ILMU KESEHATAN, 2022)
Background: The Rhesus blood group system is determined by the presence or absence of the D-antigen, and has clinical importance because it can cause Haemolytic Transfusion Reaction (HTR) and Haemolytic Disease of the Newborn (HDN). There are several variants of the D-antigen which are weak, so it will be detected as Rhesus Negative.Objective: The purpose of this study was to determine the prevalence of the Rhesus D weak blood group variant in DKI Jakarta Province, so that it could determine the identity status of the blood group correctly.Methods: The samples used in this study were whole blood samples with a maximum storage time of three days in the blood refrigerator. The examination used in this study is the Indirect Antiglobulin Test (IAT).Results: Rhesus Dweak variant was detected in 103 samples examined using the IAT examination method.Conclusion: Determination of the Rhesus variant in individuals is necessary to prevent clinical impact on the patient. Further examination is needed to ensure the D-antigen of the Rhesus blood group